COVID-19 and Islamic Banking Services: Digitalisation as a Post-Crisis Solution (Case of Morocco) - AMRANI, OUMNIYA; Najab, Amal (European Journal of Islamic Finance, 2020)
Movement restrictions and the resulting social distancing, as measures to flatten the curve of the spread of coronavirus disease 2019 (COVID-19), highlighted 'electronic business models' (e-BM) as well as the importance of digital transformation of banking services. This article aims to empirically explore the new business opportunities offered by the digitalization of Islamic banking services as a solution to revitalize post-COVID-19 activity and overcome the difficulties of the period. The article presents the results of an opinion survey conducted among Moroccan citizens to collect and analyze their perceptions and expectations about the digital transformation of participatory banking services. This is the first exploratory study in Morocco focused on customer’s expectations regarding the digitalization of participatory banking services. The results of the survey highlighted a significant interest from customers and prospects for digital transformation of the services offered by the actors of this new banking industry, in particular through mobile banking application. However, there is still a part that prefers traditional on-site banking services .Furthermore, digital transformation also presents some risks such as cyber security and issues of non-compliance with banking regulations relating to opening a bank account remotely. To manage these risks and reshape their BM, it is recommended that participatory banking institutions set up an integrated digital strategy, improve their internal processes and equip themselves with a robust, interactive and locked information system.